Construction of China’s Carbon Financial Accounting System from the Perspective of Sustainable Development - Li, Shuwen (Problemy Ekorozwoju, 2024)
Carbon Financial Accounting System highlights the importance of carbon finance and carbon accounting in China's efforts towards sustainable development and reducing its carbon footprint. The article discusses the need to manage and trade carbon assets, develop a comprehensive carbon financing system, and account for and report carbon activities. It proposes constructing a carbon accounting framework that includes all key sources of carbon emissions and carbon sequestration capacity. The article emphasizes the need to integrate carbon accounting into a company's operations and establish a comprehensive carbon finance ecosystem as a critical component of national strategic development. To achieve this, the Chinese government must promote CDM initiatives and relevant policies, enhance support to intermediary institutions, centralize the management of CDM projects, and strengthen carbon financing regulations. The article suggests establishing carbon trading and pricing mechanisms and improving the carbon trading system to create an effective carbon finance regulatory structure. Additionally, a carbon accounting system is required for financial and accounting oversight to support green and low-carbon growth, hence strengthening carbon accounting and reporting regulations of companies. The incorporation of carbon exchange, carbon funds, and carbon sinks banks are also essential in enhancing the financial accounting system.